PENGARUH LIQUIDITY, PROFITABILITY, LEVERAGE TERHADAP FINANCIAL DISTRESS - Aryani, Assyfa; Sihono, Agus (Jaksya: Jurnal Akuntansi Syariah, 2024)
It is critical to be aware of the elements that affect a company's financial situation in today's fast-paced business climate. This is because there is a chance of financial difficulties, which might affect the stability of the company. Aiming to investigate the impact of liquidity, profitability, and leverage on financial distress in consumer goods industry enterprises, this research is a quantitative study. Secondary data culled from business financial filings is used in this study. Companies listed on the Indonesia Stock Exchange for consumer products from 2020 to 2022 make up the sample for this study. This study makes use of the purposive sampling strategy. Twenty businesses' worth of financial report data made up the study's sample. Multiple linear regression is used for the study. According to the study's findings, liquidity alleviates financial hardship. When it comes to money problems, profitability is a good thing. Leverage does not impact financial hardship. In order to foresee and avert financial difficulties, this study is helpful for a corporation. And it is believed that it may assist current and future investors in choosing which businesses to put their money into, particularly by highlighting the importance of  the liquidity and profitability factors in this study, which should lead to more targeted investments that provide the expected returns.